Pengaruh Teknik Relaksasi Benson terhadap Intensitas Nyeri Insersi AV Fistula pada Pasien Hemodialisa di RSUD Batang - Madnur Soleh; Dwi Retnaningsih (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Malaria is a global health problem, especially in tropical countries like Indonesia. Papua, with 14,586 cases, and Jayapura City in 2023 had 29,938 cases. This is due to nocturnal activities, knowledge, and preventive measures, which contribute to the high incidence of malaria. The purpose of this study was to identify factors associated with malaria incidence at Bhayangkara Hospital Class II, Jayapura. This research was an analytical study with a cross-sectional design. Data collection was conducted using a questionnaire. A total of 82 respondents were recruited using a simple accidental sampling technique. The data obtained were statistically analyzed using the chi-square test. Based on the analysis results, it was found that of the 82 respondents, the characteristics of the respondents were mostly aged > 20 years (74 people (90.2%), male (48 people (58.5%) and unemployed (53 people (64.6%). There was a significant relationship between nighttime activities and malaria incidence at Bhayangkara Hospital Level II Jayapura. (p-value 0.015 <α (0.05). There was a significant relationship between knowledge and malaria incidence at Bhayangkara Hospital Level II Jayapura (p-value 0.000 <α (0.05). There was a significant relationship between malaria prevention measures and malaria incidence at Bhayangkara Hospital Level II Jayapura (p-value 0.008 <α (0.05). Nighttime activities, knowledge and malaria prevention measures were significantly associated with malaria incidence.